Contenido de carbono y nitrogeno de la biomasa microbiana en suelos de La Habana - Gomez Jorrin, L.A.=700 1 Morales valdes, A.; Dueñas Vega, G.; Dantin Martinez, J.M.; Chavez Gonzalez, N.; Torres Leblanch, M.
(Es, En)
Ilus., 34 ref.
Keywords: SUELO; ANALISIS DEL SUELO; CARBONO; CONTENIDO DE NITROGENO; BIOMASA; METODOS; FUMIGACION; EXTRACCION; ACRISOLES; CUBA